A novel yield optimization technique for digital CMOS circuits design by means of process parameters run-time estimation and body bias active control. - Olivieri, M. (IEEE Transactions on VLSI systems)
This work presents a novel approach to optimize digital integrated circuits yield referring to speed, dynamic power and leakage power constraints. The method is based on process parameter estimation circuits and active control of body bias performed by an on-chip digital controller. The associated design flow allows us to quantitatively predict the impact of the method on the expected yield in a specific design. We present the architecture scheme, the theoretical foundation, the estimation circuits used, and two application case studies, referring to an industrial 0.13-μm CMOS process data. The approach results to be remarkably effective at high operating temperature. In the presented case study, initial yields below 14% are improved to 86% by using a single controller and a single set of estimation circuits per die.